Comparative Performance of Water Hyacinth (Eichhornia crassipes) and Water Lettuce (Pista stratiotes) in Preventing Nutrients Build‐up in Municipal Wastewater. Issue 4 (28th July 2014) - Ismail, Zubaidah; Othman, Siti Zulaikha; Law, Kim Hing; Sulaiman, Abdul Halim; Hashim, Roslan
<x xml:space="preserve">Abstract</x> Studies on removal of nutrients from domestic wastewater using water hyacinth (Eichhornia crassipes) and water lettuce (Pista stratiotes) were conducted. The plants were grown in 68 L of wastewater with 21‐day retention period in fiber‐glass tanks with another similar tank as control. Eichhorniacrassipes performed better than P. stratiotes in reducing the concentrations of nitrate‐nitrogen and ortho‐phosphates while P. stratiotes performed better than E. crassipes in reducing the concentrations of ammoniacal‐nitrogen (NH4‐N) and nitrite‐nitrogen. On average, E. crassipes reduced the NH4‐N concentration by 72%, P. stratiotes reduced the concentration by 83% and the concentration in the control was reduced by 95%. On average, E. crassipes reduced the phosphate concentration by 55%, P. stratiotes reduced the concentration by 60% and the concentration in the control increased by 28%. Algae significantly reduced the concentration of NH4‐N.